The influence of the plates on the effectiveness of penetrating thermoelements in the cooling regime - Semeshkin, V.A.; Cherkez, R.G.; Zhukova, A.S.; Stefiuk, V.V. (Physics and Chemistry of Solid State, 2023)
This paper describes the physical model of the penetrating thermoelement with the developed surface of warmth exchange for the cooling of the air’s flow. It presents the theory of the calculation and the method of the computer modeling of the temperature’s and potential’s allocation, the definition of the effectiveness of the energy’s transformation – the cooling factor and the cooling efficiency. This work researches the 3D temperature’s and materials’ allocation for the material of the branches of the thermoelement based on Bi2Te3.